2003
DOI: 10.1093/ajcn/77.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of waist circumferences measured at 4 sites

Abstract: WC values at the 4 commonly used anatomic sites differ in magnitude depending on sex, are highly reproducible, and are correlated with total body and trunk adiposity in a sex-dependent manner. These observations have implications for the use of WC measurements in clinical practice and patient-oriented research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
396
2
20

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(455 citation statements)
references
References 24 publications
29
396
2
20
Order By: Relevance
“…The latter aspect is also complicated by the heterogenity of anatomical measurement sites (e.g. midpoint between the lowest rib and the iliac crest, as suggested by the WHO, or immediately above the iliac crest, as recommended by NIH guidelines and NHANES III) (see Wang et al 41 for review).…”
Section: Value Of Fm Vs Anthropometric Obesity Indices For Assessmentmentioning
confidence: 99%
“…The latter aspect is also complicated by the heterogenity of anatomical measurement sites (e.g. midpoint between the lowest rib and the iliac crest, as suggested by the WHO, or immediately above the iliac crest, as recommended by NIH guidelines and NHANES III) (see Wang et al 41 for review).…”
Section: Value Of Fm Vs Anthropometric Obesity Indices For Assessmentmentioning
confidence: 99%
“…61 Exact location of the measuring tape continues to be debated. A recent study 62 of 111 able-bodied males and females 7-83 years determined that waist circumference values measured at four sites (immediately below the lowest rib, at the narrowest waist, midpoint between the lowest rib and the iliac crest and immediately above the iliac crest) had equally high reproducibility and were almost equally associated with total body fat and trunk fat in each sex. The authors noted that of the 14 anatomical locations commonly reported in the literature, the narrowest waist is the most frequently recommended.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
“…Several indexes enable to identify overall obesity (or excessive weight), such as body mass index (BMI), which is the most used one for being easy to obtain and apply, and also due to its good correlation with body fat measurements 6 . For abdominal obesity, isolated waist circumference (WC) values are often used in epidemiological studies 7 .…”
Section: Introductionmentioning
confidence: 99%